Windbreak Designs and Planting for Florida Agricultural Fields - Bijay Tamang; Michael G. Andreu; Melissa H. Friedman; Donald L. Rockwood (EDIS)
FOR-227, a 6-page illustrated fact sheet by Bijay Tamang, Michael G. Andreu, Melissa H. Friedman, and Donald L. Rockwood, reviews several design and planting options in order to assist in windbreak planning and development. Includes references. Published by the UF School of Forest Resources and Conservation, August 2009.